Riverbed Scour Due to Accumulation of Floating Debris on Al-Msharah Bridge Piers - Nama, Ala Hassan; Abdulhussain, Zahraa (Nahrain University College of Engineering Journal, 2015)
This paper aims to implementing and run a study hydraulic simulation model by using the HEC-RAS software to simulate the flow in AL-Msharah River and studying the effect of floating debris accumulation on Al-Msharah Bridge piers on the flow conditions upstream the bridges and estimating the scour development according to this effect.All the required geometric, hydrological and riverbed material data were provided by Ministry of Water Resources, Iraq. These data were adopted for implementing the hydraulic simulation model. The effects of debris accumulation at the bridge piers were studied according to the present state of the river through considering six inflow discharge 5, 10, 15, 20, 25, and 30 m3/sec each with a range of floating debris dimensions (width, m × depth, m) up to (2m×2m).Results of applying the implemented hydraulic model showed that accumulation of debris on the bridge piers for more than 1m×1m increase the water surface elevation upstream the bridge to about 1m with the case of maximum discharge of 30m3/sec and debris of 2m×2m and increase the flow velocity and changing the flow velocity distribution within the bridge cross-section by about 15 to 20%.The total main channel scour depth increase from 0.77 m for the case of no debris with minimum discharge, 5 m3/sec, to 1.9 m for the case of 2m×2m debris with maximum discharge, 30 m3/sec.According to these results it is recommended that accumulated debris on AL Msharah Bridge piers must be carefully monitoring when its dimensions became more than 1m×1m and it must be removed from the bridge piers when its dimensions become more than 2m×2m because the resulted scour damage the bridge